Indonesia's Rising Divide - World Bank (World Bank, Jakarta, 2016)
In 2015, Indonesia stands as an increasingly divided country, unequal in many ways. There is a growing income divide between the richest 10 percent and the rest of the population, and this gap is driven by many other types of inequality in Indonesia.People are divided into haves and have-nots from before birth. Some children are born healthy and grow up well in their early years; many do not. Some children go to school and receive a quality education; many do not. In today’s modern and dynamic economy; most do not and are trapped in low-productivity and low-wage jobs. Some families have access to formal safety nets that can protect them from the many shocks that occur in life; many do not. And a fortunate few Indonesians have access to financial and physical assets (such as land and property) that increase their wealth over time. This wealth is passed down from generation to generation, both in the form of money and physical assets, and through greater access to better health and education. As a result, inequalities are being compounded and deepened over time. This report asks why inequality is increasing, why it matters, and what can be done. The first section examines the trend in inequality, which is already relatively high in Indonesia and rising more rapidly than in many neighboring countries. The second section seeks to understand what is driving rising inequality in Indonesia. The final section looks at what can be done to prevent the country from becoming even more divided. This section suggests ways to avoid an Indonesia in which relatively few people are healthy, happy and prosperous, and many more can only aspire to a better life but are unable to attain it.